TI_GERICHTE 52.2009.350 vom 26. April 2010 , Ripetizione di una classe di scuola media di un allievo su richiesta dei genitori - TI Tribunale d'appello (2010)
Ripetizione di una classe di scuola media di un allievo su richiesta dei genitori